Identification of batik making method from images using convolutional neural network with limited amount of data - Mohammad Arif Rasyidi; Ruktin Handayani; Fauzul Aziz (Institute of Advanced Engineering and Science, 2021)
This study aims to apply the convolutional neural network (CNN) to classify batik based on its manufacturing method, namely Batik Tulis which are hand drawn, Batik Cap where stamps are used to create the pattern, and Batik Printing which are printed using textile printing machine. We collected 40 images for each type of batik with a total of 120 images. To speed up and simplify the model building process, we implemented transfer learning with 3 basic CNN model architectures, namely ResNet, DenseNet, and VGG with batch normalization. We also experimented with building a new dataset by breaking each image down into 30 smaller images. Image augmentation was also used to prevent overfitting as well as to provide variations in the training data. The experimental results with 5-fold cross validation show that densenet169 gives the best results on the original dataset with an accuracy of 79.17% while vgg13_bn shows the best performance on the modified dataset with an accuracy of 87.61%. All models showed an increase in performance when using the modified dataset, except densenet169 which did not show a significant difference in performance.